Experimental characterization and modeling of the plastic behavior of a thirdgeneration advanced high strength steel sheet - Santos, Rafael Oliveira (2022)
The third generation of the advanced highstrength steels (AHSS) has attracted the automotive industry attention owing to its good compromise between the formability and production cost. The current development stage of these steels so far has few products available on the market, as well as little research aimed at studying their formability. With an ultimate tensile strength greater than 1000 MPa and total elongation above 20%, the thirdgeneration AHSS with 980 MPa grade was the first sheet of this class of steel to be commercialized. In this work, several mechanical tests were performed to analyze the plastic behavior of a coldrolled Gen3 980T steel with a nominal thickness of 1.58 mm. The mechanical properties and the plastic anisotropy Lankford coefficients were obtained from uniaxial tensile tests performed in 7 angular orientations in the plane of the sheet. The workhardening of the Gen3 980T steel sheet was also assessed by means of the hydraulic bulge test, and the biaxial anisotropy coefficient was obtained using the disc compression test. The formability was investigated by means of the hole expansion, Erichsen cupping, and forming limit curve (FLC) test procedures. The limit strains were defined by ISO 120042 standard from inplane tests (uniaxial tension and plane strain in tension) and out of plane hemisphericalpunching tests (Nakajima procedure). The GursonTvergaardNeedleman (GTN) damage model was adopted to describe the fracture behavior of the Gen3 980T steel. A simple methodology for identifying the parameters of the GTN model was proposed. This calibration procedure was validated by comparing finite element predictions with the experimental measurements obtained from the mechanical tests. The Gen3 980T steel has a microstructure composed of martensite, ferrite, and retained austenite. In the asreceived condition, the Xray diffraction analysis provided 12.2% of the retained austenite volume fraction. In the sheet rolling direction, the average values of the yield stress () and ultimate tensile strength () are equal to 604 and 1040 MPa, respectively, along with a total elongation ( ) of 23.4%. In this way, Gen3 980T steel has global formability, defined by = 24.3 GPa%, a value which is consistent with that expected for the thirdgeneration of advanced highstrength steels. The Lankford coefficients determined in the angular orientations 0, 45, and 90 degrees with respect to the rolling direction are very close, which provided planar and normal anisotropy coefficients of − 0,079 and 0.917, respectively. The hole expansion ratio (HER) determined for the Gen3 980T steel sheet was equal to 10.9%, whereas the corresponding average Erichsen cupping test index (EI) was equal to 10.62 mm. The numerical simulations were able to describe the increase in formability due to the reduction of the friction coefficient and the effects inherent to the Nakajima test sample's curvature. The GTN damage model parameters, identified from the experimental uniaxial tensile data, provided a good forecast of the experimental results located on the lefthand side of the FLC. Regarding the right side of the FLC, the results obtained for the limit strains were conservative, mainly for the equal biaxial stretching.